2020
DOI: 10.12659/ajcr.925779
|View full text |Cite
|
Sign up to set email alerts
|

Three Cases of Pediatric Multisystem Inflammatory Syndrome Associated with COVID-19 Due to SARS-CoV-2

Abstract: Case series Patients: Male, 7-year-old • Female, 6-year-old • Male, 5-year-old Final Diagnosis: Multisystem inflammatory syndrome in children (MIS-C) Symptoms: Heart failure Medication: — Clinical Procedure: — Specialty: Pediatrics and Neonatology Objective: Unusual clinical course Background: Coronavirus disease 2019 (COVID-19) infection commonly presents as fev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 11 publications
0
25
0
4
Order By: Relevance
“… N.A. [ 213 ] 1 (non-confirmed) F 7 PIMS-TS IVIg, glucocorticoids, ASA Recovered [ 214 ] 3 (2 confirmed) 2 M 1 F 6y PIMS-TS 2 shock IVIg, ASA Recovered [ 215 ] 570 (565 confirmed) 316 M 254 F 8y MIS-C 202 shock 424 IVIg, 331 glucocorticoids, 309 ASA 10 Deaths 95 Coronary artery abnormalities [ 216 ] 30 (2 confirmed) 12 M 2 F 2y 22 complete KD, 8 atypical KD 30 IVIg, 14 IVIg + glucocorticoids, Recovered 2 Coronary artery aneurysms [ 217 ] 25 (17 confirmed) 15 M 10 F 12.5y MIS-C 23 IVIg, 20 glucocorticoids, 10 TCZ, 4 infliximab, 1 anakinra Recovered 7 Coronary artery abnormalities [ 218 ] 11 (all confirmed) 9 M 2 F 59m PIMS-TS, 5 shock N.A. 2 Deaths [ 219 ] 1 (confirmed) M 45y KD IVIg, TCZ, topical glucocorticoids Recovered [ …”
Section: Resultsmentioning
confidence: 99%
“… N.A. [ 213 ] 1 (non-confirmed) F 7 PIMS-TS IVIg, glucocorticoids, ASA Recovered [ 214 ] 3 (2 confirmed) 2 M 1 F 6y PIMS-TS 2 shock IVIg, ASA Recovered [ 215 ] 570 (565 confirmed) 316 M 254 F 8y MIS-C 202 shock 424 IVIg, 331 glucocorticoids, 309 ASA 10 Deaths 95 Coronary artery abnormalities [ 216 ] 30 (2 confirmed) 12 M 2 F 2y 22 complete KD, 8 atypical KD 30 IVIg, 14 IVIg + glucocorticoids, Recovered 2 Coronary artery aneurysms [ 217 ] 25 (17 confirmed) 15 M 10 F 12.5y MIS-C 23 IVIg, 20 glucocorticoids, 10 TCZ, 4 infliximab, 1 anakinra Recovered 7 Coronary artery abnormalities [ 218 ] 11 (all confirmed) 9 M 2 F 59m PIMS-TS, 5 shock N.A. 2 Deaths [ 219 ] 1 (confirmed) M 45y KD IVIg, TCZ, topical glucocorticoids Recovered [ …”
Section: Resultsmentioning
confidence: 99%
“…Levels of many cytokines have been found to be increased in severe, critically ill and fatal cases 14,22,156,166,171 . Of note, there are emerging reports of a rare systemic inflammatory condition in children, resembling typical or atypical Kawasaki disease, presently named Pediatric Inflammatory Multisystem Syndrome temporally associated with SARS‐CoV‐2 infection (PIMS‐TS), toxic shock syndromes, bacterial sepsis and macrophage activation syndromes (http://www.rcpch.ac.uk/resources/guidance-paediatric-multisystem-inflammatory-syndrome-temporally-associated-covid-19) 77,106,107,111,114,203,209‐229 of whom some but not all test positive for COVID‐19. The clinical characteristics of PIMS‐TS include cardiac disease sometimes including coronary artery aneurysms, the need for intensive care and inotrope, and additional treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphocytopenia was observed in 7 patient and lymphocytosis in one patient. Heidemann et al (USA) [ 9 ] 3 3 6 (5y-7y) 1:2 1 Prolonged fever was observed in 2 of 3 patients. Echocardiography showed decreased left ventricular function in all patients.…”
Section: Appendix Amentioning
confidence: 99%